Enhancing Vocational Students' Speaking Performance Through Instagram Reels: Evidence of Significant Fluency Improvement - Pasya Oktaverina; Zulia Chasanah; Sri Widodo (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Speaking proficiency remains a major challenge for vocational EFL learners, particularly in fluency, pronunciation, and confidence. This study examined the effectiveness of Instagram Reels in improving students’ speaking performance. Methods: A quasi-experimental non-equivalent control group design was applied to two intact eleventh-grade classes at SMK Negeri 8 Purworejo. The experimental group learned speaking through Instagram Reels, while the control group received conventional instruction. Data were collected through pre-test and post-test speaking assessments using an analytic rubric covering pronunciation, grammar, vocabulary, fluency, and comprehensibility, then analyzed with descriptive statistics, paired-sample t-tests, independent-sample t-tests, and N-gain. Results: The experimental group achieved greater improvement than the control group, with a higher post-test mean score (85.30 and 72.10), a significant difference (p < 0.05), and a high N-gain score of 0.70. Conclusion: Instagram Reels is an effective digital medium for improving vocational students’ speaking performance, especially fluency, and supports its integration into English instruction in meaningful short-video practice contexts.